2003
DOI: 10.1108/09590550310461994
|View full text |Cite
|
Sign up to set email alerts
|

Generation Y female consumer decision‐making styles

Abstract: Since environmental factors have influenced Generation Y shoppers (those born after 1977) to make them different from older groups, this study examines the decision making of Adult Female Generation Y consumers using Sproles and Kendall's (1986) Consumer Styles Inventory (CSI). The study uses the CSI as a basis for segmenting Generation Y consumers in to five meaningful and distinct decision-making groups, namely:``recreational quality seekers'',``recreational discount seekers'',``trend setting loyals'',``shop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
311
2
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(336 citation statements)
references
References 38 publications
13
311
2
10
Order By: Relevance
“…Such opportunities are also significant for the long-term future of the wine industry and wine tourism because of the potential for consumption habits, such as drinking wine and visiting wineries, to be maintained over a cohort as the cohort grows older (e.g. GLENN, 1977;GILLEARD;HIGGS, 2002;BAKEWELL;MITCHELL, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Such opportunities are also significant for the long-term future of the wine industry and wine tourism because of the potential for consumption habits, such as drinking wine and visiting wineries, to be maintained over a cohort as the cohort grows older (e.g. GLENN, 1977;GILLEARD;HIGGS, 2002;BAKEWELL;MITCHELL, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Generation Y consumers, research has demonstrated that individuals within this age cohort display differing shopping orientations, thereby provoking the need for more extensive empirical introspection (Jin & Kim, 2003). More specifically, Generation Y consumers have been brought up in an era when shopping has evolved from being a simple act of purchasing to a highly complex and sophisticated process (Bakewell & Mitchell, 2003). There are at least three reasons for conducting this study.…”
Section: Research Problemmentioning
confidence: 99%
“…The underlying determinants of how and why people shop has been a topic of study for many years (Bakewell & Mitchell, 2003). In the context of Generation Y consumers, research has demonstrated that individuals within this age cohort display differing shopping orientations, thereby provoking the need for more extensive empirical introspection (Jin & Kim, 2003).…”
Section: Research Problemmentioning
confidence: 99%
“…Millennials are said to have been heavily influenced by the Great Recession (Archer, 2017). More than half of the millennials in our survey sample reported that one or both of their parents had lost a job at some This has led to an explosion of research about the attitudes and opinions of millennials as employees (Ertas, 2015;Myers and Sadaghiani, 2010), consumers (Bakewell and Mitchell, 2003;Gurău, 2012;Noble, Haytko, and Phillips, 2009), and citizens (Jennings and Stoker, 2004). In 2013, Time magazine put millennials on a cover that derided the "Me, Me, Me Generation" as "lazy, entitled narcissists" (Stein, 2013).…”
Section: Baby Boommentioning
confidence: 99%